Os homens negros em Ponciá Vicêncio e Canção para ninar menino grande, de Conceição Evaristo - Paslawski, Luana Gabriela (2024)
This thesis analyzes the fictionalization of black men in Conceição Evaristo's novels Ponciá Vicêncio and Big boy lullaby, emphasizing the intersections of gender, race, and class oppression. It examines how these forces limit the characters' ability to conform to hegemonic masculine ideals of control, violence, and hypersexuality. Acknowledging that black men are also socially constructed and can perpetuate sexism, the thesis calls for a rethinking of traditional masculinity models. Drawing on black feminist thinkers like bell hooks (2022), Lélia Gonzalez (2020), and Carla Akotirene (2021), as well as Silvio Almeida's (2021) critique of structural racism, this study explores how shared experiences of oppression could pave the way for a more egalitarian coexistence between black men and women. This analysis challenges the hierarchies established when difference is perceived as inferiority, leading to subordination. Employing the theoretical framework of Literary Studies, this research utilizes exploratory, analytical, and comparative readings of the primary texts and relevant critical works.